A comparative study on L-thyroxine treatment and sesame oil supplementation in experimentally induced hypothyroidism in rats - Lasheen, Noha N.; Shawky, Sara; Gaber, Noha; Mohamed, Abd El-Hamid A. (Frontiers in Physiology, 2025)
Background and AimsNatural antioxidants have gained increasing attention in medical and nutritional research. Sesame oil, a supplement widely recognized for its anti-inflammatory and antioxidant properties, remains underexplored with respect to its potential role in hypothyroidism management. Levothyroxine is currently the mainstay of therapy for hypothyroidism. Based on this, we aimed to demonstrate the effects of different treatments on the systemic parameters, including the liver and heart, of hypothyroid rats and to elucidate the underlying mechanisms.MethodologyAdult female Wistar rats (n = 66) were randomly allocated into control, sesame oil-treated euthyroid, propylthiouracil-induced hypothyroid, L-thyroxine-treated hypothyroid, sesame oil-treated hypothyroid, and combined treated hypothyroid groups. After 8 weeks, arterial blood pressure values were measured using a noninvasive rat tail sphygmomanometer. On the day of sacrifice and after overnight fasting, rats were anesthetized with pentobarbitone, and electrocardiograms were recorded. Separated plasma samples were used to measure the thyroid hormone levels, cardiac and liver enzymes, lipid profile, oxidative stress markers, and interleukin-6. Hepatic low-density lipoprotein receptor concentration and hepatic stearoyl-CoA desaturase 1 gene expression were determined, in addition to histopathological studies of heart and liver tissues.ResultsPrimary hypothyroidism was evident in the hypothyroid group, whereas all treated groups were euthyroid. Compared to the control group, the hypothyroid group exhibited systolic hypotension, diastolic hypertension, arrhythmia, higher cardiac enzymes, dyslipidemia, impaired liver functions, upregulated hepatic stearoyl-CoA desaturase 1 expression, lower hepatic low-density lipoprotein receptor concentration, cardiomyopathy, and focal hepatic fibrosis. Both L-thyroxine and sesame oil showed cardioprotective and hepatoprotective effects, whereas sesame oil exhibited greater lipolytic effects by enhancing low-density lipoprotein receptor concentration; both caused downregulated hepatic stearoyl-CoA desaturase 1 gene expression. Hypothyroid-induced oxidative stress was limited in all treated groups, whereas sesame oil had additional anti-inflammatory effects. Synergistic lipolytic effects and better control of diastolic blood pressure were observed in the hypothyroid group treated with the combination.ConclusionSesame oil has the potential to be utilized as an adjuvant therapy with L-thyroxine to counteract the cardiac and hepatic alterations induced by hypothyroidism. This is supported by its antioxidant, anti-inflammatory, and antisteatotic characteristics.